Trends, risks and prospects for industrial complex development of south of Russia in new economic realities - Mitrofanova, Inna V.; Chernova, Olga A.; Batmanova, Victoria; Trilitskaya, Oksana Yu. (Serbian Journal of Management, 2021)
Events caused by complex crisis which became evident in regional economies as a result of the spread of COVID-19 have affected the manufacturing industry of the South of Russia. The purpose of this article is to identify and analyse the prospects for the sustainable development of industry in the South of Russia in the context of new economic trends. The methodological basis of the study is founded on the theory of shocks, which made it possible to place at the center of the system of cause-and-effect relationships a set of factors in business activity decrease, which are considered as shocks that form new development trends. The analysis revealed the presence of problems of production interruptions and break of supply chains, reduction in resource flows, as well as a decrease in effective demand for industrial products. According to the opinion of the authors, the prospects for the development of the industrial complex of the region are associated with the balance of market self-regulation and government regulation, and are also determined by the accumulated potential of the regional industry and available adaptive capabilities.